SOCIAL CRITICISMS IN DIKIR BARAT SONG LYRICS - Norhafidah Binti Ibrahim; Norzaliza Binti Ghazali; NorAsyikin Binti Ibrahim (Journal of Islamic, Social, Economics and Development, 2018)
Dikir Barat is a very famous art in the state of Kelantan that is very much loved by various levels of society, more especially among the Malay community. The creation of lyric in this local song was not merely for entertainment. This study is conducted to identify and explain the aspects of social criticism applied in the lyrics of this song. This study analyses the content of the lyric of the song by Halim Yazid and Cikgu Naim, whose lyrics addressed a number of current issues related to life or events that occur in a society through experience and observersation. The social criticism contained in the lyrics aimed at reprimanding individuals or societies subtly such that the target individuals are not offended. This study uses a qualitative method which analyses data from lyric texts of this song lyrics. This study focuses on social criticism that involves the attitude of the leader, the society, the youth and the spirit of patriotism.